The association of socioeconomic disadvantage with postoperative complications after major elective cardiovascular surgery. Issue 10 (12th September 2008) - Agabiti, N; Cesaroni, G; Picciotto, S; Bisanti, L; Caranci, N; Costa, G; Forastiere, F; Marinacci, C; Pandolfi, P; Russo, A; Perucci, C A; ,
Abstract : Background: Understanding the mechanism by which both patient- and hospital level factors act in generating disparities has important implications for clinicians and policy-makers. Objective: To measure the association between socioeconomic position (SEP) and postoperative complications after major elective cardiovascular procedures. Design: Multicity hospital-based study. Subjects: Using Hospital Discharge Registries (ICD-9-CM codes), 19 310 patients were identified undergoing five cardiovascular operations (coronary artery bypass grafting (CABG), valve replacement, carotid endarterectomy, major vascular bypass, repair of unruptured abdominal aorta aneurysm (AAA repair)) in four Italian cities, 1997–2000. Measures: For each patient, a five-level median income index by census block of residence was calculated. In-hospital 30-day mortality, cardiovascular complications (CCs) and non-cardiovascular complications (NCCs) were the outcomes. Odds ratios (ORs) were estimated with multilevel logistic regression adjusting for city of residence, gender, age and comorbidities taking into account hospital and individual dependencies. Main results: In-hospital 30-day mortality varied by type of surgery (CABG 3.7%, valve replacement 5.7%, carotid endarterectomy 0.9%, major vascular bypass 8.8%, AAA repair 4.0%). Disadvantaged people were more likely to die after CABG (lowest vs highest income OR 1.93, p trend 0.023). For other surgeries, the relationship between SEP and mortality was less clear. For cardiac surgery, SEP differences in mortality were higher for publicly funded patients in low-volume hospitals (lowest vs highest income OR 3.90, p trend 0.039) than for privately funded patients (OR 1.46, p trend 0.444); however, the difference in the SEP gradients was not statistically significant. Conclusions: Disadvantaged people seem particularly vulnerable to mortality after cardiovascular surgery. Efforts are needed to identify structural factors that may enlarge SEP disparities within hospitals.